Impact of intrauterine exposure to the insecticide coragen on the developmental and genetic toxicity in female albino rats. Issue 1 (31st December 2022) - Omar, Amel Ramadan; Emam Dakrory, Ahmed; Abdelaal, Marwa Mohamed; Bassiony, Heba
ABSTRACT: Coragen 20 SC is a new insecticide that contains the active ingredient chlorantraniliprole, which has been approved for use against insects in many crops due to the presence of insect ryanodine receptors. The present study aims to evaluate the intrauterine exposure to coragen in pregnant rats and their fetuses from 6 th to 20 th day of gestation. The pregnant dams were orally administrated saline (control), 100 mg/kg (low dose) or 200 mg/kg (high dose) of coragen. The mothers of two treated groups showed teratogenic anomalies such as asymmetrical distribution of fetuses in the two uterine horns, as well as, observed resorption, bleeding in the uteri while, their fetuses had growth retardation, morphological malformations and some skeletal perversions in addition to some dead fetuses were recorded. Furthermore, multiple histopathological changes occurred and a significant DNA damage was induced by coragen in maternal and fetal liver and kidney tissues compared to the control. Gestational coragen treatment resulted in teratogenic and genotoxic effect on pregnant rats and their fetuses. The obtained results in the present study imply that women and their fetuses may have the same risk.